2007
DOI: 10.1534/genetics.106.067983
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modifiers of Drosophila Palmitoyl–Protein Thioesterase 1-Induced Degeneration

Abstract: Infantile neuronal ceroid lipofuscinosis (INCL) is a pediatric neurodegenerative disease caused by mutations in the human CLN1 gene. CLN1 encodes palmitoyl-protein thioesterase 1 (PPT1), suggesting an important role for the regulation of palmitoylation in normal neuronal function. To further elucidate Ppt1 function, we performed a gain-of-function modifier screen in Drosophila using a collection of enhancerpromoter transgenic lines to suppress or enhance the degeneration produced by overexpression of Ppt1 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 88 publications
(107 reference statements)
3
32
0
Order By: Relevance
“…However, it is not clear how the loss of Ppt1 activity causes retinal degeneration. It has been reported that Ppt1 and Psd interact genetically when they are overexpressed (Buff et al, 2007). Moreover, in this study, we have demonstrated that Ppt1 mutants show light-dependent retinal degeneration and that there is a genetic interaction between these genes when they are downregulated.…”
Section: Degradation Of Rhodopsin By Autophagysupporting
confidence: 66%
See 2 more Smart Citations
“…However, it is not clear how the loss of Ppt1 activity causes retinal degeneration. It has been reported that Ppt1 and Psd interact genetically when they are overexpressed (Buff et al, 2007). Moreover, in this study, we have demonstrated that Ppt1 mutants show light-dependent retinal degeneration and that there is a genetic interaction between these genes when they are downregulated.…”
Section: Degradation Of Rhodopsin By Autophagysupporting
confidence: 66%
“…The genetic interaction between the Psd and Ppt1 loss-offunction alleles was examined because a previous study described an interaction between overexpressed Ppt1 and Psd (Buff et al, 2007). To test this, dsRNAs for Psd and Ppt1 were induced simultaneously using weak conditions under which expression of each one of the dsRNAs did not cause severe defects (Fig.…”
Section: Overexpression Of Rab7 Rescues Retinal Degeneration Caused Bmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Gain-of-function genetic screens in the fly have implicated Ppt1 function in the regulation of several neuronal processes, including synaptic growth/homeostasis and synaptic vesicle endo/exocytosis. 22,23 An examination of non-neuronal larval garland cells in Ppt1 mutants showed reduced endocytosis rates, without alterations in endo-lysosomal trafficking. 23 Similarly, alterations in endocytosis have been observed in fibroblasts from INCL patients.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this precise control is borne out by the many examples of defects in post-translational lipid modifications that are linked to neurodegenerative diseases, such as Schizophrenia, X-linked mental retardation, Huntington disease, as well as colorectal and bladder cancers (Buff, et al, 2007;Williams, 1991). Despite significant progress in identifying the enzymes involved in post-translational lipid modification, their specific protein targets and the relationship between lipid modifications and membrane targeting remain unclear.…”
Section: H]-fpp or [ 3 H]-ggpp)mentioning
confidence: 99%